Nicotinic Treatment for Cognitive Dysfunction - Levin, E.D.; Rezvani, A.H. (Current Drug Targets-CNS & Neurological Disorders, 2002)
Nicotinic medications may provide beneficial therapeutic treatment for cognitive dysfunction such as Alzheimer's disease, schizophrenia and attention deficit hyperactivity disorder (ADHD). For development of nicotinic treatments we are fortunate to have a well characterized lead compound, nicotine. Transdermal nicotine patches offer a way to deliver measured doses of nicotine in a considerably safer fashion than the more traditional means of administration, tobacco smoking. We have found that transdermal nicotine significantly improves attentional function in people with Alzheimer's disease, schizophrenia or ADHD as well as normal nonsmoking adults. To follow-up on this proof of principal that nicotinic treatment of cognitive dysfunction holds promise, it is important to use animal models to determine the critical neurobehavioral bases for nicotinic involvement in cognitive function so that more selective nicotinic analogues that improve cognitive function with fewer side effects can be developed. We have found with local infusion in rat studies that the hippocampus and amygdala are important substrates for nicotinic effects on working memory function. Both α7 and α4β2 nicotinic receptors are involved in working memory. Nicotinic interactions with dopaminergic and glutaminergic systems are also important in the basis of cognitive function. Studies of the neural nicotinic mechanisms underlying cognitive function are key for opening avenues for development of safe and effective nicotinic treatments for cognitive dysfunction.
Keywords: Alzheimers Disease